Significant Details from the biography of Romanos Melikyan - Sukiasyan Համո Կարենի (Musical Armenia, 2025)
From the early 1920s onwards, the perfonnance of works with spiritual and religious themes was discouraged in Soviet Armenia as part of a broader effort to instill communist ideology among the populace. This policy extended even to the musical legacy of prominent composers. Romanos Melikyan, a composer and the head of the Conseivatoiy at the time, had a deep admiration for the work of Makar Yekmalyan and took active measures to collect, study, and promote his musical legacy. In Januaiy-Februaiy 1924, while serving as the Conseivatoiy’s head, Melikyan initiated the organisation of a concert evening dedicated to Yekmalyan’s compositions. Having obtained preliminary permission from the People’s Commissariat of Enlightenment (Narkompros) for the event, he proceeded, out of prudence, to seek formal approval from the Central Committee of the Communist Party of Armenia. This action, however, provoked a stem response from the Narkompros Askanaz Mravyan, who reprimanded Melikyan for approaching the higher Soviet and Party authorities on behalf of the Conseivatoiy without first securing permission from the People’s Commissariat of Enlightenment. Disheartened by the severity of the reprimand, Romanos Melikyan submitted his resignation from the position of head of the Conseivatoiy on 21 July 1924.